The Individuated, Messianic Servant of OG Isaiah 48–49 - Martin, Michael W. 1971- (2025)
In this study I argue that OG Isaiah in its rendering of chaps. 48-49 presents the servant as both a true individual and the Lord's messianic agent in the world. In chap. 48, OG Isaiah recasts the clearly collectivist "servant Jacob" as an individual distinct from the nation and a Moses-like agent of a new exodus. In chap. 49, OG Isaiah enhances and clarifies features suggestive of individualist interpretation (contrary to scholarly opinion on the matter), thereby aligning chap. 49 more clearly with chap. 48. Further, in the course of individuating the servant, OG Isaiah transfers aspects of both Israel's and Yhwh's eschatological rule and salvation to the figure. These changes serve to recast the servant as a "messiah" in the strict sense of the term.
Keywords: Isaiah; Old Greek; Septuagint; Messiah; Messianism; Servant